Visual bone marrow mesenchymal stem cell transplantation in the repair of spinal cord injury - Zhang, Rui-ping (Neural Regen Res, 2015)
An important factor in improving functional recovery from spinal cord injury using stem cells is maximizing the number of transplanted cells at the lesion site. Here, we established a contusion model of spinal cord injury by dropping a weight onto the spinal cord at T(7-8). Superparamagnetic iron oxide-labeled bone marrow mesenchymal stem cells were transplanted into the injured spinal cord via the subarachnoid space. An outer magnetic field was used to successfully guide the labeled cells to the lesion site. Prussian blue staining showed that more bone marrow mesenchymal stem cells reached the lesion site in these rats than in those without magnetic guidance or superparamagnetic iron oxide labeling, and immunofluorescence revealed a greater number of complete axons at the lesion site. Moreover, the Basso, Beattie and Bresnahan (BBB) locomotor rating scale scores were the highest in rats with superparamagnetic labeling and magnetic guidance. Our data confirm that superparamagnetic iron oxide nanoparticles effectively label bone marrow mesenchymal stem cells and impart sufficient magnetism to respond to the external magnetic field guides. More importantly, superparamagnetic iron oxide-labeled bone marrow mesenchymal stem cells can be dynamically and non-invasively tracked in vivo using magnetic resonance imaging. Superparamagnetic iron oxide labeling of bone marrow mesenchymal stem cells coupled with magnetic guidance offers a promising avenue for the clinical treatment of spinal cord injury.